Chasing the white rabbit to find a white elephant: Exploring limited/non-use of education technology in Mpumalanga, South Africa - Nimmo, Peter (Graduate School of Business (GSB), 2019)
This qualitative, inductive dissertation explores a social enterprise’s management of for-profit and not-for-profit missions administered through different programmes. Ineffective balancing negatively impacted the design, development, and implementation strategy of an education technology (EDTech) trial in no-fee government schools in Mpumalanga, South Africa intended to fund a non-profit music academy. This study builds upon existing literature in information technology management; the implications of managing multiple missions in social enterprises; as well as technology design and development theory. These are used to offer a descriptive account of limited/non-use of education technology in areas facing deep rooted inequalities. Through adopting a qualitative methodology using semi-structured interviews, observation, and document analysis; rich data was gathered to construct three case studies of individual schools. These case studies are compared to the expectations and reflections of the social enterprise’s board and management in light of limited/non use of EDTech. The research finds high degrees of nuance between schools; even within 5 Kilometres of each other. Such nuance is reflected in uneven provision of devices, educational resources, and infrastructure; varying technology integration strategies between schools; in addition to the individualistic sensemaking of education technology by teachers. This research provides a rich example of the difficulty for social enterprises in balancing disintegrated social and commercial value chains. This increases the risk of such organisations ineffectively allocating resources by prioritising speculative financial gain over social impact; resulting in failure to achieve multiple, differentiated missions.